Application of Public Relations Management Concept as A Communication Strategy for Corporate Social Responsibility Campaign #BeautyDiQuity PT Luxury Cantika Indonesia (Luxcrime) - Wibowo, Wini Elia; Permassanty, Tanty Dewi (Global Research on Economy, Business, Communication, and Information, 2023)
Luxcrime conducted a public relations program campaign, in 2023 by choosing the campaign moment to coincide with International Women's Day with the theme "Beauty in Diversity and Equality" #BeautyDiQuity which means that beauty in diversity and equality. In the #BeautyDiQuity campaign, Luxcrime invited five disabled models to campaign for beauty in diversity and equality, Luxcrime also invited the audience to take part and support the #BeautyDiQuity program by buying International Women's Day Bundle products which later ten percent of the revenue will be donated to the Unique Project Theatre Foundation and Nali Tari Yogyakarta. The response obtained through the BeautyDiQuity CSR event as part of Luxcrime's public relations activities was positive and supported. Where Luxcrime celebrates the diversity of beauty. This is already based on CSR activities that have previously been carried out by Luxcrime. So the expected response from this activity remains oriented to the Luxcrime brand image as a brand that upholds empowerment values and not just selling.